Vision system for detection known household objects in natural indoor environments - Wang, Hui. (2010)
In the last decade of years, object recognition is a popular subject. It can support either blind people or robotic devices with possibility to search for known objects in indoor environments, or image searching on the internet(goggle.com). The author develops a system that can detect known object based on previous algorithms.